Processos de imitação das ações de cuidado pelos bebês na educação infantil - Larissa Monique de Souza Almeida Ribeiro (2022)
This thesis sought to understand the genesis of the processes of imitation of care actions by babies during the experiences of collective practices of education and care in a Municipal School of Early Childhood Education (EMEI Ciranda) in Belo Horizonte. We base our theoretical and methodological conceptions on principles of the Historical-Cultural Approach (VIGOTSKI, 1929, 1934/2010 and TOMASELLO 2003, 2005) and Ethnography in Education (GREEN; DIXON; ZAHARLICK, 2005). The Historical-Cultural Approach allows us to understand that man is an aggregate of social relations constructed dialogically with the Other. In a dialectical way, the interest is in the process of changes and transformations and in what it triggers in the human constitution. Ethnography in Education is understood as a logic of investigation, an epistemology that involves recognition of the Other, to support the description of the ways of life of the social group researched. Our defense is that, as an essential factor, imitating presupposes a certain understanding of the meaning of the action of the other, that is, it is the basis by which man appropriates knowledge and develops as a human (VIGOTSKI, 1934/2010). Therefore, imitation is an activity aimed at some objective that, based on perception and action in the world, babies appropriate the adult's intentional action and create means to achieve it, representing their entry into the cultural world with and through of the Other (TOMASELLO, 2003). The field investigation took place in a group of babies over two years (2017-2018). We identified, in the researched group, different forms of cultural appropriation in the interaction between peers, adults, cultural artifacts and languages. We analyzed, in a more specific way, the construction of a narrative around the care shared between them, evidenced through body expression, gestures, movements, shared caresses, in a structured and repeated process of care practices that assumed centrality in the researched group. The analysis of the events points to the thesis that imitation is a complex activity that synthesizes different cultural functions during interactions in the contexts of collective education and care. It is characterized as one of the founding ways of the babies' cultural development that engenders the experiences and enables actions in the perceptual and imaginary field. in interactions established in social practices (between peers, adults and materialities) In this sense, imitation is constituted by the unit [affect/located social cognition/cultures/languages in use (ACCL)] (GOMES; NEVES, 2021).